Quantitative Proteomic Profiling of Cerebrospinal Fluid to Identify Candidate Biomarkers for Alzheimer's Disease. Issue 4 (25th January 2019) - Sathe, Gajanan; Na, Chan Hyun; Renuse, Santosh; Madugundu, Anil K.; Albert, Marilyn; Moghekar, Abhay; Pandey, Akhilesh
Abstract : Purpose: The aim of this study is to identify the potential cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease and to evaluate these markers on independent CSF samples using parallel reaction monitoring (PRM) assays. Experimental Design: High‐Resolution mass spectrometry and tandem mass tag (TMT) multiplexing technology are employed to identify potential biomarkers for Alzheimer's disease. Some of the identified potential biomarkers are validated using PRM assays. Results: A total of 2327 proteins are identified in the CSF of which 139 are observed to be significantly altered in the CSF of AD patients. The proteins altered in AD includes a number of known AD marker such as MAPT, NPTX2, VGF, GFAP, and NCAM1 as well as novel biomarkers such as PKM and YWHAG. These findings are validated in a separate set of CSF specimens from AD dementia patients and controls. NPTX2, in combination with PKM or YWHAG, leads to the best results with AUCs of 0.935 and 0.933, respectively. Conclusions and Clinical Relevance: The proteins that are found to be altered in the CSF of patients with AD could be used for monitoring disease progression and therapeutic response and perhaps also for early detection once they are validated in larger studies.